The gods of the Greeks - Simon, Erika, 1927-2019 (Wisconsin studies in classics., 2021)
"Originally published in Germany fifty years ago, The Gods of the Greeks has remained an enduring work. Influential scholar Erika Simon was one of the first to emphasize the importance of analyzing visual culture alongside literature to better understand how ancient Greeks perceived their gods. Giving due consideration to cult ritual and the phenomenon of genealogical relationships between mortals and immortals, this pioneering volume remains one of the few to approach the Greek gods from an archaeological perspective. From Zeus to Hermes, each of the major deities is considered in turn, with Simon's insights on their nature and attributes guiding the reader to a fuller understanding of how their followers perceived and worshipped them in the ancient world. This careful and fluid translation finally makes Simon's landmark edition accessible to English-language readers. With an abundance of beautiful illustrations, the book examines portrayals of the thirteen major gods in art over the course of two millennia. Scholars who study the lives and practices of those living in ancient Greece will value this newest contribution."--Publisher description